EFEKTIVITAS PENYALURAN ZAKAT SEBAGAI BANTUAN MODAL USAHA KEPADA PEDAGANG KAKI LIMA (PKL) OLEH BADAN AMIL ZAKAT NASIONAL (BAZNAS) DALAM PROGRAM LAHAT PEDULI DI KABUPATEN LAHAT - Prayoga, Rendi; Muslih, Akhmad; Arso, Dimas Dwi (UNIB Press, 2023)
The poverty rate is still very large in Indonesia, this is due to the still high unemployment rate and this situation is getting worse with the Covid-19 outbreak which threatens the whole world. One of the efforts that can be made by the community in an effort to fulfill their daily needs is to become street vendors (PKL). However, they also have obstacles in running their business because they still have limited capital and this can be helped by providing business capital assistance whose sources of funds come from zakat where the institution that manages zakat funds is the National Zakat Amil Agency (BAZNAS). The purpose of this research is to find out whether the distribution of zakat funds as venture capital assistance to MSME actors by BAZNAS in the Lahat Care program in Lahat Regency has yielded effective results or not. As well as how the responsibility of BAZNAS Lahat Regency in terms of distribution of zakat funds. The type of research used in this research is empirical law. In empirical legal research law is conceptualized as an empirical phenomenon that can be observed in real life, law is empirically a symptom of society, on the one hand it can be studied as an independent variable or cause (independent variable) which gives rise to consequences in various aspects of social life. As a result, from the process of collecting zakat funds to distributing zakat funds to business actors, it has had an effective impact, many have benefited from the Lahat Cares program from BAZNAS. The SIMBA application (BAZNAS Management Information System) is an online integrated application that can be accessed by the public as a form of BAZNAS' responsibility to show transparency.